Is There a Relationship Between Social Capital and Organizational Citizenship Behavior ?: An Empirical Study from Legislature Member - Khairul - Amri; Nurmala Nurmala (Universitas Sultan Ageng Tirtayasa, 2021)
Social capital is very important for every individual including members of the legislature. Theoretically and referring to the findings of previous studies organizational citizenship behavior is positively related to the social capital. Until now no studies have examined the relationship between social capital and organizational citizenship behavior on legislature. This paper presents the empirical findings on the relationship between social capitals with organizational citizenship behavior among legislature member in the Aceh province of Indonesia. The samples of the study are 243 legislature members from 23 districts in Aceh Province. The data collection utilizes questionnaires. We employed structural equation modeling for the research framework and AMOS was used to analyze the model. Our study reveals that social capital significantly related to organizational citizenship behavior.